Competing at altitude reduces in-match physical demands of professional soccer players compared with sea level - Silva, H.; Girard, O.; Monteiro, J.; Gasques, M.; Sousa, A.; Nakamura, F. Y. (International Journal of Sports Physiology and Performance, 2025)
Purpose This study examined whether physical demands during soccer matches differ between sea level and altitude, considering variations by playing position.